Job satisfaction in conventionally employed and teleworkers: the impact of gender, age and education - Srđana Taboroši; Jovanka Popović; Jasmina Poštin; Marko Konjikušić; Milan Nikolić (Anali Ekonomskog fakulteta u Subotici, 2022)
This paper examines and analyzes the differences in job satisfaction among conventionally employed and teleworkers. Differences were examined for three control variables: gender, age, and education of the respondents. The research was conducted in West Balkan countries (Bosnia and Herzegovina, Croatia, Montenegro, North Macedonia, and Serbia), and included 313 respondents (conventionally employed and teleworkers). Teleworkers are more satisfied than conventionally employed. This is most evident through satisfaction with all forms of compensation, procedures, and associates. Job satisfaction is higher in men, both who work conventionally and who telework. Men are significantly more appreciative of opportunities for advancement, as well as achieving additional benefits and rewards. Younger respondents have greater job satisfaction than older respondents, this only applies to conventionally employed. There are no differences in job satisfaction within teleworkers, depending on their age. Job satisfaction does not depend on the level of education of the respondents, and this applies to both conventionally employed and teleworkers. Companies that apply telework more objectively evaluate the results of their employees' work and the contribution they provide to the company, and in accordance, they adequately reward and promote employees. Thus, all age and educational categories of employees see their chance in teleworking conditions.